Multiparametric MRI characteristics of prostatitis and atrophy in the peripheral zone in men without prostate cancer - Monajjed, Rouvier Al-; Radtke, Jan Philipp; Thomas, M.; Boschheidgen, Matthias; Drewes, L; Ullrich, T; Rau, T.; Esposito, Irene; Antoch, Gerald; Albers, P.; López-Cotarelo Rodríguez-Noriega, Cristina; Schimmöller, Lars (European journal of radiology, 2023)
Purpose - To analyse multiparametric magnetic resonance imaging (mpMRI) characteristics and appearance of histopathologically proven non-cancerous intraprostatic findings focussing on quantity of prostatitis and atrophy in the peripheral zone. - Method - In this retrospective analysis consecutive patients with mpMRI followed by MRI/TRUS-fusion biopsy comprising targeted (TB) and systematic biopsy (SB) cores without prostate cancer (PC) at histopathology were included. Subgroup analysis was performed in younger men (≤50 years). The proportions of prostatitis and atrophy were quantified for each biopsy core based on histopathology. MRI findings in the peripheral zone (PZ) and index lesions (IL, most suspicious/representative lesion) were characterized regarding changes in T2w, ADC value, and enhancement of dynamic contrast enhancement (DCE) and correlated with quantity of prostatitis and atrophy. - Results - Seventy-two patients were analysed. The median baseline characteristics were PSA 5.4 ng/ml (4.0-7.9), PI-RADS classification 3 (2-4), prostate volume 43 ml (33-57), and PSA density 0.13 ng/ml2 (0.10-0.19). Prostatitis was found in 44 % (n = 32) and atrophy in 65 % (n = 47) of cases. The quantity of atrophy demonstrated a significant correlation to T2w changes, ADC increase and DCE enhancement (p = 0.05, p = 0.05, p = 0.01), whereas quantity of prostatitis did not show any significant correlation to the MRI changes (p = 0.68, p = 0.58, p = 0.95). Quantity of prostatitis and atrophy increased with PI-RADS classification. Younger men had lower PSA (4.4 vs. 7.8 ml/ng; p < 0.001), smaller prostate volume (40 vs. 59 ml; p = 0.001), and lower PI-RADS classification (2-3 vs. 3-4; p = 0.005) and prostatitis and atrophy were less frequently observed (p ≤ 0.01, p = 0.03). - Conclusions - Quantity of atrophy and prostatitis had different influence on MRI characteristics and increased within higher PI-RADS classification. Younger men had diffuse hypointense changes at T2w images, but less quantity of prostatitis and atrophy.